Безумное пари: роман / Татьяна Туринская - Туринская Татьяна (Русский Арлекин, 2007)
Экземпляры: ф.14 (20141205) / Инвентарный номер: 51278 / Цена: 21. 00. / Сис.шифр: Р2 / Авт.знак: Т 87 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4